Zooplankton products on certain sections of the «Dnipro-Donbas» canal - Novitsky, R. A.; Novitsky, R. O.; Novitskiy, R. A.; Novitskiy, R. O.; Novickii, R. A.; Novitskij, R. A.; Novitskij, R. O.; Nowicki, R. A.; Novickij, R. A.; Novitskyy, R. O.; Novitskyi, R. O.; Novitsky, Roman O.; et al. (Дніпровський ДАЕУ, 2020)
In May 2020 the quantitative and qualitative composition of zooplankton as a food item of aquatic bioresources was determined in the water area of the «Dnipro-Donbas» hydrotechnical canal. As a result of complex hydrobiological researches it was revealed that there are significant changes in the number of all groups of aquatic organisms, including zooplankton. 14 species of zooplankton were found. Taxonomic diversity is represented by three groups of Rotatoria, Cladocera, Copepoda. It was proved that climate change, wide fluctuations of water temperature have led to a decrease in the number and species diversity of zooplankton. The quantitative and qualitative composition of zooplankton is also affected by periodic pumping of water along the canal route. It was noted that planktonic organisms affect the level of eutrophication of the canal and the amount of oxygen in the aquatic environment; they form secondary products in the reservoir. It was established that the amount of 108 000 item/m3 and zooplankton biomass of 781 mg/m3 in the water area of different sections of the «Dnipro-Donbas» hydrotechnical canal are insufficient. When determining the groups of zooplankton, it was found that the roe of rotifers (Rotatoria) was the most numerous in the sampling sections, and in the area № 2 (Shulhivka Bridge area) in the spring it was completely absent. The maximum indicators of zooplankton number and biomass were observed in the section of the canal upper Shulhivka Bridge (59 000 item/m3, 506.87 mg/m3). The area of the canal near Shulhivka Bridge was characterized by the smallest quantitative development of zooplankton species (8 000 items/m3, 53.7 mg/m3). There were no rotifers in that area. Seasonal features of the frost-free and snowless winter of 2019–2020, warm spring of 2020 caused disbalance in the functioning of the aquatic ecosystem; it affected the formation of biological products of the canal and its consumption by the final link of trophic chains (fish). У травні 2020 року на акваторії гідротехнічного каналу «Дніпро-Донбас» визначали кількісний та якісний склад зоопланктону як кормового об’єкту водних біоресурсів. У результаті комплексних гідробіологічних досліджень виявлено, що відбуваються значні зміни чисельності всіх груп гідробіонтів, у тому числі зоопланктону. Знайдено 14 видів-зоопланктерів. Таксономічне різноманіття представлено трьома групами – Rotatoria, Cladоcera, Copepoda. Доведено, що зміни клімату, різкі коливання температури води привели до зменшення чисельності та видового різноманіття зоопланктону. На кількісний та якісний склад зоопланктону впливає також періодичне прокачування води по трасі каналу. Зазначено, що планктонні організми впливають на рівень евтрофікації каналу, кількість кисню у водному середовищі та формують вторинну продукцію у водоймі. Встановлено, що кількість 108 000 екз/м3 та біомаса зоопланктону 781 мг/м3 на акваторії різних ділянок гідротехнічного каналу «Дніпро-Донбас» недостатні. При визначенні угруповань зоопланктерів встановлено, що найчисельнішими в місцях відбору проб були яйця коловерток (Rotatoria), а на ділянці№ 2 (район Шульгівського мосту) навесні вони взагалі відсутні. Максимальні показники кількості та біомаси зоопланктону відзначені на ділянці каналу вище Шульгівського мосту (59 000 екз/м3, 506,87 мг/м3). Найменшим кількісним розвитком видів-зоопланктерів характеризується ділянка каналу поблизу Шульгівського мосту (8 000 екз/м3, біомаса – 53,7 мг/м3. Коловертки відсутні). Сезонні особливості безморозної та безсніжної зими 2019–2020 рр., теплої весни 2020 року обумовили дисбаланс у функціонуванні водної екосистеми, який вплинув на утворення біологічної продукції каналу та споживання її кінцевою ланкою трофічних ланцюгів (рибою).
Продукція зоопланктону на окремих ділянках каналу «Дніпро-Донбас»
Новіцький Роман Олександрович https://orcid.org/0000-0001-9373-5759 Губанова Надія Леонідівна https://orcid.org/0000-0003-0617-2498 Горчанок Анна Володимирівна https://orcid.org/0000-0003-0103-1477
Keywords: the «Dnipro-Donbas» canal; канал «Дніпро-Донбас»; productivity; продуктивність; zooplankton; зоопланктон; rotifers; коловертки; copepods; веслоногі ракоподібні; water fleas; гіллястовусі ракоподібні; Copepoda; Copepoda; Cladocera; Cladocera; Rotatoria; Rotatoria